A method for geometric calibration of edge‐on detectors in a CT‐gantry. Issue 11 (28th October 2016) - Sjölin, Martin; Danielsson, Mats
Abstract : Purpose: Photon‐counting edge‐on detectors are currently being considered for use in clinical computed tomography (CT) systems. A method for geometric calibration of edge‐on detectors mounted on a CT‐gantry has been developed and evaluated. The method is complementary to the geometrical calibration methods developed for CT systems using flat‐panel detectors and takes the extra dimension of the edge‐on detectors (along the direction of the x‐rays) into account. Methods: The method uses projection images of a simple phantom together with geometrical arguments to accurately estimate the orientation and relative position of the edge‐on detectors. Both computer simulations and experimental measurements were used to verify the method. Results: It is experimentally demonstrated that the method can determine the orientation of the detector with an accuracy of 0.08°. The method is also shown to be insensitive to errors in the modeled parameters used in the algorithm. Conclusions: The presented method can accurately determine the orientation and relative position of edge‐on detectors mounted on a CT‐gantry and can be used to evaluate the detector mounting and to produce an accurate forward model of the imaging system. Also, the method has potential to reduce the dimensionality of the geometric calibration of the full CT system since the direction of the x‐rays with respect to the detector is measured.